2016
DOI: 10.4103/1735-1995.193513
|View full text |Cite
|
Sign up to set email alerts
|

The transtheoretical model, health belief model, and breast cancer screening among Iranian women with a family history of breast cancer

Abstract: Background:Participation of Iranian women with a family history of breast cancer in breast cancer screening programs is low. This study evaluates the compliance of women having a family history of breast cancer with clinical breast exam (CBE) according to the stage of transtheoretical model (TTM) and health belief model (HBM).Materials and Methods:In this cross-sectional study, we used Persian version of champion's HBM scale to collect factors associated with TTM stages applied to screening from women over 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…cues to action such as information, past health behaviour) influence an individual’s perceptions of illness susceptibility and severity, benefits of treatment, and barriers to accessing treatment. There is a growing body of evidence indicating that the HBM can accurately predict physical health help-seeking behaviours, such as those relating to healthy eating (Mascioli & Davis, 2019), vaccinations (Scherr et al ., 2017), and breast screening (Farajzadegan et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…cues to action such as information, past health behaviour) influence an individual’s perceptions of illness susceptibility and severity, benefits of treatment, and barriers to accessing treatment. There is a growing body of evidence indicating that the HBM can accurately predict physical health help-seeking behaviours, such as those relating to healthy eating (Mascioli & Davis, 2019), vaccinations (Scherr et al ., 2017), and breast screening (Farajzadegan et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The American Cancer Society (ACS) recommends mammography in women aged 40 years and above annually and CBE every 3 years by health professionals in 20s and 30s lifelong and after the age of 40 years every year. [ 6 7 ] Although BSE practice as a screening test can increase the probability of detecting breast cancer at an early stage by women themselves, it is associated with an increased number of biopsies for benign breast lesions and increased physician visits. Furthermore, mammography and CBE facilitate early detection and treatment of breast cancer and thus reduce the mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that the rate of participation in breast cancer screening programs is low in this at risk group ( 6 ). Several studies have shown that women’s knowledge, perceived level of sensitivity, risk perception, health motivation, and potential benefit and harm from screening method influence their willingness to participate in breast cancer screening programs ( 7 - 9 ).…”
Section: Introductionmentioning
confidence: 99%